Tree communities in Baltimore differ by land use type, but change little over time. Issue 4 (27th April 2022) - Jiang, Shasha; Sonti, Nancy F.; Avolio, Meghan L.
Abstract: Across a city, tree communities are spatially heterogenous and vary by land use type. However, it remains unclear how urban tree communities change over time and whether rates of change depend on land use type. To address this knowledge gap, we analyzed urban tree composition using long‐term plot data to examine tree diversity changes across six different urban land use types in 1999, 2004, 2009, and 2014. We found that spatial differences in tree species diversity and community composition among land uses were much greater than changes over time. Number of trees increased over time, being driven by gains of non‐native species. There was also a significant interaction between land use and time, with institutional and transportation land uses having greater community changes over time. Our study can inform site‐specific efforts to promote and preserve urban biodiversity across public and private land uses.